Faktor Komunikasi Efektif dalam Meningkatkan Kinerja Pegawai - Cyrious Cyrious; Erica Adriana (GEMILANG: Jurnal Manajemen dan Akuntansi, 2023)
Effective communication is an important factor in improving employee performance in an organization. This study aims to describe the factors of effective communication that play a role in improving employee performance. The method used in this study is literature analysis which includes scientific articles and research related to effective communication and employee performance. The findings from this literature study indicate that factors such as open, clear, and open communication between superiors and subordinates, the use of appropriate communication media, active involvement in communication, and the ability to listen empathetically can contribute to improving employee performance. The implication of this finding is the importance of paying attention to and improving effective communication within organizations to achieve optimal employee performance.